2021
DOI: 10.1186/s12906-021-03287-1
|View full text |Cite
|
Sign up to set email alerts
|

The use of herbal and dietary supplement among community-dwelling elderly in a suburban town of Malaysia

Abstract: Background The use of herbal and dietary supplement (HDS) in health and disease management has gained global attention. HDS are generally accepted by the public and are associated with positive health behaviours. However, several reports have been documented with regards to their potential adverse effects and interaction with conventional medicines. Limited data is currently available on the use of HDS among elderly population in Malaysia. This present study aims to investigate the prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 47 publications
2
19
2
Order By: Relevance
“…Clinical studies focusing on phytochemicals in flap surgery are still rare, even though the favorable risk–benefit profile of phytochemicals would make them good candidates for the treatment of patients ( Wahab et al, 2021 ). Indeed, from the compounds addressed, only three have been tested in human studies in the context of flap surgery, i.e., salvianolic acid B, TMP, and hydroxysafflor yellow A ( Chen et al, 2010 ; Ma et al, 2010; Shining and Zha, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies focusing on phytochemicals in flap surgery are still rare, even though the favorable risk–benefit profile of phytochemicals would make them good candidates for the treatment of patients ( Wahab et al, 2021 ). Indeed, from the compounds addressed, only three have been tested in human studies in the context of flap surgery, i.e., salvianolic acid B, TMP, and hydroxysafflor yellow A ( Chen et al, 2010 ; Ma et al, 2010; Shining and Zha, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we observed that individuals living in suburban areas were less likely to consult CPs about HDSs than those living in urban areas. This is a concern because in Malaysia, HDSs are prevalently used among those living in suburban areas [ 1 , 61 , 62 , 63 ]. While no data can be compared directly to our result, in a study conducted in Michigan, USA, Malewski et al, reported that individuals who lived in a suburban area were less likely to seek advice from CPs about medications than those who lived in an urban area [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Herbal and dietary supplements (HDSs) are widely used in Malaysia [ 1 , 2 , 3 ] as well as in other countries [ 4 , 5 , 6 ]. HDS products are readily accessible over the counter with no prescription required to obtain them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a study reported that 44.5% of Malaysian patients consumed dietary supplements (DS), whereas 24.9% used HS to manage medical conditions including diabetes mellitus, dyslipidaemia, and peripheral neuropathy [ 6 ]. Furthermore, the use of HDS is prevalent among the elderly [ 7 , 8 ], pregnant women [ 9 ], and breastfeeding mothers [ 10 ]. As reported in previous studies, a growing interest and positive attitude towards HDS are two main reasons for the widespread use of HDS among the public and patients.…”
Section: Introductionmentioning
confidence: 99%